QUALITY MANAGEMENT OF LEARNING AS AN EFFORT TO INCREASE SCHOOL ACCREDITATION VALUE DURING THE PANDEMIC - Hatta Fakhrurrozi; Fikri Hamdani (Paedagogia: Jurnal Pendidikan, 2022)
This research was inspired by the phenomenon of the COVID-19 pandemic and the continuity of learning in remote schools, which was related to an increase in school accreditation. This type of research is qualitative and uses a naturalistic approach. This multi-site research examines two schools, SMPN 3 Satap Banawa Tengah and SMPN 11 Satap Palolo. The focus of this research is to find out the practice of quality management of education in both schools to answer the research questions as: 1) management of the learning process during a pandemic; 2) correlation of learning process management with school accreditation. Research data was collected using structured interviews, observation, and documentation. The data was analyzed using data reduction, presentation, and triangulation. This study found that quality management of the learning process was consistently carried out at the school during the pandemic. Both schools have implemented limited semi-online learning. Limited semi-online learning has similarities with other online learning but also has differences in implementation aspects. The second finding, every step taken by the principal in managing the learning process, refers to the accreditation guidelines that the ministry of education and culture has set. The analysis is carried out by critiquing each question item in the accreditation guidelines and is adjusted to the steps taken by the school. In practice, it's hard for schools to meet some of the accreditation requirements. However, in terms of the formal parts of the learning process, every step schools have taken has met the criteria set by the ministry of education.